The electric vehicle transition in Russia and Indonesia - Ashurzoda Shahboz; Raldi Hendrotoro Seputro Koestoer (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Due to worries about global warming and its effects on the environment, economy, and society, a lot of emphasis has been paid to the switch to electric vehicles (EVs). This essay focuses on the switch to electric vehicles in Indonesia and Russia. Green technology, such as EVs, have been introduced in Indonesia in order to lower carbon dioxide (CO2) emissions and enhance air quality. The study emphasizes the advantages of EVs, including their simplicity and improved comfort when compared to conventional vehicles, as well as their free highway use, parking, and tax incentives. The restricted affordability, ambiguous national policies, and inadequate public infrastructure provide difficulties for Indonesia. However, relative to its enormous auto fleet, Russia has lagged behind in the development of EVs, with just a tiny number of registered electric vehicles. However, the Russian government has approved a plan to increase the infrastructure and production of electric road transport. The strengths, weaknesses, and transitional strategies for EVs are assessed using a case study approach and comparative analysis. In order to encourage the use of EVs, it is stressed the significant of incentive programs and supportive policies, such as tax breaks and regional manufacture. The study comes to the conclusion that although both nations have made progress in the transition to electric vehicles, more has to be done in terms of policy creation, infrastructure development, and technological improvements in order to hasten the adoption of EVs in Russia and Indonesia.